Testing international arbitrage: evidence from Chinese and Australian markets - Abraham, Santosh Mon (Curtin University, 2014)
This paper studies two contrarian strategy; one based on the Law of One Price and another based on the Markov switching strategy. The stock pairs are identified using a new derivation of the partial adjustment model. The Markov strategy is more profitable than the LOP strategy. This paper also tests international momentum effects between Chinese Shanghai Composite Index and Australian resource stocks. The enhanced indexing strategy is more profitable than the index tracking strategy.